P109 Introduction of an electronic patient proformer contributes to an increase in uptake of HIV testing. (23rd May 2012) - Bhatt, S; Clarke, E; Roseaman, K; Patel, R; Samraj, S
Abstract : Background: The BASHH MEDFASH Standards for the Management of STIs 2010 recommend that 100% of GUM patients should be offered an HIV test with a minimum uptake of 60% at their first STI screen. Aim: To assess whether the introduction of an electronic patient proformer resulted in an improvement in the uptake of HIV testing in a level 3 GUM service, and whether there was scope for further improvement. Methods: Retrospective case note review of new and rebook (patients who had not attended in the past 3 months) patients attending a level 3 GUM service in October 2007 (when a paper patient record was kept) and October 2010 (following introduction of an electronic patient proformer with a prompt for HIV test offered). Data on uptake of HIV testing was collected, and further data on the reasons for not being tested for HIV was collected on patients seen in October 2010. Results: 772 new or rebook patients were seen in October 2007, of whom 562 (72.8%) accepted HIV testing. 1141 new or rebook patients were seen in October 2010 of whom 891 (78.1%) accepted HIV testing, with a p value (calculated using Fisher's Exact test) of 0.009. Of 250 (21.9%) patients not tested for HIV in October 2010, 41.6% were not tested for clinical reasons, such as the patient having had a recent HIV test or being known HIV positive. 35.2% of patients not tested for HIV declined the test. Evidence of suboptimal management was also found, with 6.8% of patients not tested as they were within the window period, and 6% not tested due to needle phobia. Conclusion: The introduction of the electronic patient proformer with a prompt for HIV testing has improved uptake. There is further room for improvement including offering POCT to needle phobic patients, and testing those within the window period prior to follow-up testing. Adding a mandatory field to the patient proformer with reasons for declining may allow improved understanding of reasons for declining, which may then modify future practice.